A public policy approach to understanding the nature and causes of foreign policy failure. Issue 5 (27th May 2016) - McConnell, Allan
ABSTRACT: All governments are vulnerable to policy failure but our understanding of the nature and causes of policy failure is highly underdeveloped. This contribution, written from a public policy perspective, sets out a framework for understanding these issues as applied to foreign policy. In doing so, it seeks a cross-disciplinary fertilization of thinking that uses the messy and contested reality of policy failure as fundamentally a key – rather than a barrier – to advancing our understanding of a phenomenon referred to variously as policy fiascos, policy disasters, policy blunders and policy failures.